18p Deletion Syndrome With Concurrent Frizzled-4 Mutation Surgical Management of Bilateral Stage 5 Traction Retinal Detachment - Wakabayashi, Taku (Ophthalmic surgery, lasers & imaging retina, 2023)
We report a case of a patient with 18p deletion syndrome and concurrent FZD4 (frizzled-4) mutation. A 6-month-old boy with known 18p deletion syndrome presented with abnormal eye movements in both eyes and an inability to track objects. The patient had a history of laryngomalacia, hypotonia, and developmental delay. Examination showed bilateral total exudative and traction retinal detachment with anomalous retinal vascular development noted on widefield fluorescein angiography. Genetic analysis identified a concurrent FZD4 mutation (c.205C>T [p.H69Y]). Both eyes underwent 25-gauge limbal vitrectomy, lensectomy, and membrane peeling, and the posterior pole successfully reattached with improvement in visual function. The 18p region contains the LAMA1, TGIF1, and APCDD1 genes, which are involved in the vascular basement membrane and Wnt/β-catenin signaling, which may have potentiated the particularly severe familial exudative vitreoretinopathy phenotype. We present the clinical findings, imaging analyses, and surgical management of concurrent 18p deletion syndrome and FDZ4 mutation. The overlap in molecular mechanisms of the multiple gene products may potentiate the severe phenotype. [Ophthalmic Surg Lasers Imaging Retina 2023;54:284-290.]